Styrene‐butadiene‐styrene copolymer compatibilized interfacial modified multiwalled carbon nanotubes with mechanical and piezoresistive properties. Issue 5 (30th September 2015) - Wang, Lun; Wang, Zhe; Wang, Yue; Wang, Xue; Wang, Hengwei; Lu, Guoming; Zhao, Dongyu; Li, Zewen
ABSTRACT: In this study, styrene‐butadiene‐styrene tri‐block copolymer/multiwalled carbon nanotubes (SBS/MWNTs) were prepared by means of a solution blending method. To enhance the compatibility between SBS and MWNTs, the SBS grafted MWNTs (SBS‐ g ‐MWNTs) were used to replace MWNTs. The MWNTs were chemically hydroxylated by the dissolved KOH solution with ethanol as solvent and then reacted with 3‐Aminopropyltriethoxysilane (APTES) to functionalize them with amino groups (MWNT‐NH2 ). The SBS‐ g ‐MWNTs were finally obtained by the reaction of MWNT‐NH2 and maleic anhydride grafted SBS (MAH‐ g ‐SBS). The SBS‐ g ‐MWNTs were characterized by X‐ray photoelectron spectroscopy (XPS), Fourier transform‐infrared spectroscopy (FT‐IR), transmission electron microscopy (TEM), scanning electron microscope (SEM), and thermogravimetric analysis (TGA). The results showed that the SBS molecules were homogeneously bonded onto the surface of the MWNTs, leading to an improvement of the mechanical and electrical properties of SBS/SBS‐ g ‐MWNTs composites due to the excellent interfacial adhesion and dispersion of SBS‐ g ‐MWNTs in SBS. A series of continuous tests were carried out to explore the electrical‐mechanical properties of the SBS/SBS‐ g ‐MWNTs composites. We found out that, near the percolation threshold, the well‐dispersed SBS/SBS‐ g ‐MWNTs composites showed good piezoresistive characteristics and small mechanical destructions for the development of little deformation under vertical pressure. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 42945. Abstract :